Structural Determinants in the Calcitonin Receptor-Like Receptor (Crlr) Important for Cgrp and Adrenomedullin (Am) Receptor Function of Crlr/Receptor-Activity-Modifying Protein (Ramp) 1 and Crlr/Ramp2 Heterodimers - W. Born; K. Leuthauser; R. Gujer; R. Muff; J.A. Fischer (The Scientific World Journal)
Cell surface protein cross-linking, coimmmunoprecipitation, and confocal microscopy identified CRLR/RAMP1-, CRLR/RAMP2-, and calcitonin receptor isotype 2 (CTR2)/RAMP1 heterodimers as CGRP-, AM-, and CGRP/amylin receptors, linked to cAMP production. Along these lines, effects of structural alterations in the N-terminal extracellular domain of the human CRLR on cell surface expression as well as the association with RAMP and CGRP or AM have been investigated.